Prosedur TEVAR pada Diseksi Aorta Klasik tipe B Kronis - Herbani, Merlita; Kurnianingsih , Novi (Jurnal Klinik dan Riset Kesehatan, 2024)
Introduction : Type B aortic dissection still become health burden that can cost quality of life. In this case, TEVAR procedure still become treatment of choice if indicated. However, TEVAR in chronic type B aortic dissection still often questioned between advantage and complication. Case Illustration : A 42 year old man with complaints of chest pain, was diagnosed with Chronic Type B Aortic Dissection. The TEVAR procedure is performed on the patient, with clinical and radiological indications. A CT scan evaluation was performed 3 months later and found closure of the false lumen, and the left kidney received collateral vascularization with a reduction in size. Currently the patient does not complain of any symptoms. Discussion : The TEVAR procedure for chronic type B aortic dissection according to indications can increase the patient's life expectancy. Regular evaluation is still needed for early detection of complications and evaluation of the blood vessels around the stent-graft. Conclusion : The TEVAR procedure in patients with chronic type B aortic dissection can be considered to increase patient survival.